Polyimide mixed matrix membrane, preparation method thereof and application of polyimide mixed matrix membrane in gas separation

By introducing a composite ZIF framework into a polyimide mixed matrix membrane and utilizing the synergistic effect of ZIF-L(Co) nanosheets and ZIF-67, a three-dimensional gas transport pathway is constructed, solving the problem of the difficulty in achieving both high permeability and high selectivity in existing technologies and realizing a highly efficient gas separation effect.

CN119281137APending Publication Date: 2025-01-10JIANGXI MINQIANG NEW MATERIAL TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411628640.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing polyimide hybrid matrix membranes are difficult to achieve both high permeability and high selectivity in the field of gas separation. They suffer from a 'trade-off' effect and cannot effectively control the permeability and selectivity of gases.

Method used

By introducing a composite ZIF framework into a polyimide mixed matrix adhesive, and utilizing the synergistic effect of ZIF-L(Co) nanosheets and ZIF-67, a three-dimensional gas transport pathway is constructed in the vertical direction of the film, thereby regulating the gas permeability and selectivity.

Benefits of technology

This technology achieves high permeability and high separation performance of polyimide hybrid matrix membranes, improving the efficiency and effectiveness of gas separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281137A_ABST
    Figure CN119281137A_ABST
Patent Text Reader

Abstract

The invention provides a polyimide mixed matrix membrane as well as a preparation method and application thereof in gas separation, and relates to the technical field of polyimide films. The polyimide mixed matrix membrane provided by the invention is prepared by curing and molding a polyimide mixed matrix glue solution, the polyimide mixed matrix glue solution comprises a polyimide glue solution and a composite ZIF frame dispersed in the polyimide glue solution, and the composite ZIF frame comprises a ZIF-L (Co) nanosheet and ZIF-67 which coats the surface of the ZIF-L (Co) nanosheet in situ. According to the invention, a three-dimensional gas transmission channel is synergistically constructed in the vertical direction of the film by utilizing the characteristics of homogeneity and different pore diameters of the composite ZIF frame, and the permeability and selectivity of gas can be effectively regulated and controlled, so that the purpose of high permeability and high separation performance of the polyimide mixed matrix film is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyimide films, and in particular to a polyimide mixed matrix membrane and a preparation method thereof and application thereof in gas separation. Background Art

[0002] The high requirements of many gas products in the chemical, energy, pharmaceutical and other industrial fields, such as high purity, high ratio and large output, have made gas separation technology have an increasingly greater impact on the development of modern industry. Membrane separation technology, which uses the different permeation rates of different gas molecules through the separation membrane to achieve mixed gas separation under the drive of pressure difference, is also called "green technology". Compared with traditional deep cold separation methods, pressure swing adsorption methods, solvent absorption methods, etc., membrane separation technology has the advantages of no phase change in the separation process, low energy consumption, small footprint, mild environment and low cost. Membrane separation technology is considered to be one of the most promising new technologies in the 21st century. So far, it has been widely used in the fields of hydrogen separation and recovery, carbon dioxide separation and recovery, air separation (oxygen-rich, nitrogen-rich), acidic corrosive gas separation, etc.

[0003] Polyimide (PI) is a class of aromatic heterocyclic polymer materials with an imide structure in the main chain, which is formed by the polycondensation of aromatic dianhydride and diamine monomers. Polyimide polymer membranes have good flexibility and film-forming properties, are easy to modify and modify, and have the advantages of high temperature resistance, thermal stability, solvent resistance, chemical stability, and good mechanical properties. In order to meet the application requirements in the field of gas separation, metal organic frameworks are usually incorporated into polyimide matrices to prepare mixed matrix membranes to improve the permeation separation performance of polyimide films for specific gases. Cobalt-based zeolite imidazole frameworks (ZIFs), which are characterized by tetrahedral metal ion nodes and imidazole ligands, are usually self-assembled by 2-methylimidazole and divalent cobalt ions. They have a molecular sieve-like structure and have the advantages of controllable morphology, adjustable pore size, excellent thermal stability and chemical stability. Cobalt-based zeolite imidazole framework / polyimide mixed matrix membranes can well combine the good mechanical processing properties of polymers and the high gas permeation separation performance of inorganic materials, so that they have received widespread attention in the field of gas separation. In order to further improve the gas permeation separation performance of gas separation membranes and overcome the "trade off" effect, it is necessary to develop a high-performance polyimide mixed matrix gas separation membrane. Summary of the invention

[0004] The object of the present invention is to provide a polyimide mixed matrix membrane and a preparation method thereof and application in gas separation.

[0005] In the first aspect, the present invention provides a polyimide mixed matrix membrane, which is prepared by curing and molding a polyimide mixed matrix adhesive; the polyimide mixed matrix adhesive includes a polyimide adhesive and a composite ZIF framework dispersed in the polyimide adhesive, and the composite ZIF framework includes ZIF-L(Co) nanosheets and ZIF-67 in-situ coated on the surface of the ZIF-L(Co) nanosheets.

[0006] The polyimide mixed matrix membrane provided by the present invention utilizes the characteristics of homogeneous and different pore sizes of the composite ZIF framework to collaboratively construct a three-dimensional gas transmission pathway in the vertical direction of the film, which can effectively regulate the permeability and selectivity of the gas, thereby achieving the purpose of high permeability and high separation performance of the polyimide mixed matrix membrane.

[0007] Optionally, the mass fraction of the composite ZIF framework in the polyimide mixed matrix glue is 5-40%.

[0008] Optionally, the polyimide glue solution includes an aprotic polar solvent and polyimide molding powder dissolved in the aprotic polar solvent.

[0009] Optionally, the aprotic polar solvent includes one of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone.

[0010] Optionally, the polyimide molding powder includes one of Vespel SP-1, Ultem 1000, Torlon 4203, Upimol, and Aurum PL450c.

[0011] Optionally, the solid content of the polyimide glue is 5-25%.

[0012] Optionally, the preparation method of ZIF-L(Co) nanosheets includes: mixing and dissolving cobalt salt and 2-methylimidazole, stirring for reaction, separating, washing, drying and grinding to obtain ZIF-L(Co) nanosheets.

[0013] Optionally, the cobalt salt includes one of cobalt nitrate, cobalt propionate, cobalt chloride and hydrates thereof.

[0014] Optionally, the molar ratio of the cobalt salt to the 2-methylimidazole is 1:(0.025-4).

[0015] Optionally, after the cobalt salt and 2-methylimidazole are mixed and dissolved, the concentrations of the cobalt salt and the 2-methylimidazole are independently 0.1-4 mol / L.

[0016] Optionally, the specifications of the ZIF-L(Co) nanosheets are 2-10 μm in length and 50-500 nm in thickness.

[0017] Optionally, the preparation method of the composite ZIF framework includes: performing titanate modification and / or silane modification treatment on the surface of ZIF-L(Co) nanosheets to obtain modified nanosheets; stirring and dispersing the modified nanosheets in a cobalt solution to obtain a nanosuspension; stirring and dissolving 2-methylimidazole in the nanosuspension and reacting, and then separating, washing and drying to obtain a composite ZIF framework.

[0018] Optionally, the surface of the ZIF-L(Co) nanosheets is modified with a titanate coupling agent.

[0019] Optionally, the titanate coupling agent includes one of PN-130, PN-101, and PN-102.

[0020] Optionally, the mass ratio of the titanate coupling agent to the ZIF-L(Co) nanosheets is 0.5-4%.

[0021] Optionally, the surface of the ZIF-L(Co) nanosheets is subjected to surface silane modification using a vinyl silane coupling agent.

[0022] Optionally, the silane coupling agent includes one of KH-540, KH-550, KH-560, KH-570, and KH-602.

[0023] Optionally, the mass ratio of the silane coupling agent to the ZIF-L(Co) nanosheets is 0.5-4%.

[0024] Optionally, the cobalt solute in the cobalt solution includes one of cobalt nitrate, cobalt propionate, cobalt chloride and hydrates thereof.

[0025] Optionally, the solvent in the cobalt solution includes methanol.

[0026] Optionally, the cobalt ion concentration in the cobalt solution is 0.1-4 mol / L.

[0027] Optionally, after 2-methylimidazole is stirred and dissolved in the nanosuspension, the concentration of the 2-methylimidazole is 0.1-4 mol / L.

[0028] Optionally, the mass ratio of the modified nanosheet, the cobalt solute in the cobalt solution, and the 2-methylimidazole in the nanosuspension is (0.1-1):1:(5-8).

[0029] Optionally, the composite ZIF framework further comprises a modified coating layer, wherein the modified coating layer is located between the ZIF-L(Co) nanosheets and the ZIF-67, and the ZIF-67 grows in situ on the surface of the modified coating layer.

[0030] In a second aspect, the present invention further provides a method for preparing any of the above optional mixed matrix membranes, comprising: coating a polyimide mixed matrix glue solution to form a film and then drying the film to obtain a mixed matrix membrane.

[0031] In a third aspect, the present invention further provides an application of a mixed matrix membrane in gas separation, wherein the gas separation includes separation of a mixture of hydrogen and methane and a mixture of hydrogen and nitrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM surface morphology image of the mixed matrix membrane prepared in Inventive Example 1;

[0033] Figure 2 This is a SEM cross-sectional morphology image of the mixed matrix membrane prepared in Inventive Example 1. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0035] The present invention provides a polyimide mixed matrix membrane, which is obtained by curing and molding a polyimide mixed matrix glue. In fact, when the polyimide mixed matrix membrane is cured, the polyimide mixed matrix glue is coated to form a film, and then dried to obtain the mixed matrix membrane. In fact, when the mixed matrix glue is coated to form a film, conventional methods such as brushing, rolling, and dipping can be used for coating, so that the thickness and shape of the formed mixed matrix membrane can be controlled.

[0036] In addition, when curing and forming the polyimide mixed matrix membrane, the mixed matrix glue can be coated on the smooth and clean surface of the glass plate to form a film, which is beneficial to improving the surface flatness and cleanliness of the mixed matrix membrane and facilitating the peeling of the formed mixed matrix membrane. In fact, after the mixed matrix membrane is coated on the smooth and clean surface of the glass plate, it is dried in a vacuum environment at 60-80°C for 6-12 hours to cure and form the polyimide mixed matrix membrane.

[0037] Specifically, the polyimide mixed matrix glue solution includes a polyimide glue solution and a composite ZIF framework dispersed in the glue solution. In fact, the composite ZIF framework is dispersed in the glue solution in advance, and after being cured into a film, a gas separation membrane with a polyimide glue film as a matrix can be formed. The composite ZIF framework can construct a gas transmission path in the polyimide-based membrane, thereby achieving gas penetration and separation.

[0038] In some embodiments, the mass fraction of the composite ZIF framework in the polyimide mixed matrix glue is 5-40%. In fact, by regulating the mass fraction of the composite ZIF framework, the morphology and density of the gas transmission path constructed by the composite ZIF framework in the mixed matrix membrane can be regulated, thereby effectively adjusting the separation efficiency and performance of the gas.

[0039] In some embodiments, the solid content in the polyimide glue is 5-25%. In fact, the mechanical strength of the formed mixed matrix membrane can be adjusted by adjusting the solid content in the polyimide glue. Specifically, the polyimide glue includes an aprotic polar solvent and a polyimide molding powder dissolved in the aprotic polar solvent. Directly using the molding powder is conducive to improving the convenience of preparing the polyimide glue. In fact, when preparing the polyimide glue, diamines and dianhydrides commonly used in the art can also be used for synthesis.

[0040] Specifically, the aprotic polar solvent in the polyimide includes one of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone, and the polyimide molding powder includes one of Vespel SP-1, Ultem1000, Torlon4203, Upimol, and Aurum PL450c. In fact, different basic properties can be given to the mixed matrix membrane by selecting different molding powders, but they are all conventional settings in the field and have no significant effect on the gas separation effect.

[0041] In fact, the composite ZIF framework includes ZIF-L(Co) nanosheets and ZIF-67 in situ coated on the surface of ZIF-L(Co) nanosheets. In fact, ZIF-L(Co) nanosheets and ZIF-67 are essentially the same as cobalt-based zeolite imidazole materials, but with different morphologies. By coating ZIF-67 on the surface of ZIF-L(Co) nanosheets, its morphology and pores can be modified, and then a three-dimensional gas transmission path can be constructed after solidification to form a mixed matrix membrane.

[0042] Specifically, the loading amount of ZIF-67 on ZIF-L(Co) nanosheets was 10-50%.

[0043] In some embodiments, the preparation method of ZIF-L(Co) nanosheets includes: mixing and dissolving cobalt salt and 2-methylimidazole, stirring and reacting, separating, washing, drying and grinding to obtain ZIF-L(Co) nanosheets. In fact, during the reaction, cobalt ions and 2-methylimidazole are assembled and grown through coordination bonds to form ZIF-L(Co) nanosheets, and the separation and washing processes are used to improve the purity of the nanosheets, and then the nanosheets are broken by grinding to avoid the formation of agglomerates to obtain ZIF-L(Co) nanosheets with higher dispersion.

[0044] In some embodiments, the cobalt salt includes one of cobalt nitrate, cobalt propionate, cobalt chloride and hydrates thereof, and the cobalt salt and 2-methylimidazole can be mixed and dissolved in deionized water to prepare a mixed solution for stirring reaction. In fact, a commonly used cobalt salt that can dissolve and dissociate cobalt ions and a solvent that can be used to dissolve the cobalt salt and 2-methylimidazole can be selected.

[0045] In some embodiments, when the cobalt salt and 2-methylimidazole are mixed and dissolved, the molar ratio of the cobalt salt to the 2-methylimidazole is 1:(0.025-4). Specifically, by regulating the molar ratio of the cobalt salt to the 2-methylimidazole, it is beneficial to coordinate and grow and self-assemble the nanosheets in the solution environment. Specifically, after the cobalt salt and 2-methylimidazole are mixed and dissolved, the concentrations of the cobalt salt and the 2-methylimidazole are independently 0.1-4 mol / L. In fact, the cobalt salt solution and the 2-methylimidazole solution can also be mixed and stirred for reaction.

[0046] In some embodiments, after the cobalt salt and 2-methylimidazole are mixed and dissolved and stirred for reaction, centrifugal separation, filtration separation, vacuum filtration and other separation methods commonly used in the art can be used to separate the solid and liquid of the mixed system after the stirring reaction. At the same time, the separated solid can be circulated and washed with deionized water to improve the surface purity of the solid, and dried to constant weight in an environment of 50-70°C.

[0047] Specifically, the preparation method of the composite ZIF framework includes: performing titanate modification and / or silane modification treatment on the surface of ZIF-L (Co) nanosheets to obtain modified nanosheets; stirring and dispersing the modified nanosheets in a cobalt solution to obtain a nanosuspension; stirring and dissolving 2-methylimidazole in the nanosuspension and reacting it, and then separating, washing, and drying to obtain a composite ZIF framework.

[0048] In fact, by surface modification of ZIF-L(Co) nanosheets, a modified coating layer can be formed on the surface of ZIF-L(Co) nanosheets, which is not only beneficial to improve the surface activity of ZIF-L(Co) nanosheets and promote the in situ growth of ZIF-67 on the surface of nanosheets, but also can avoid the continued growth of nanosheets on the basis of ZIF-L(Co) nanosheets, and then use ZIF-67 to modify the surface morphology and pores of ZIF-L(Co) nanosheets.

[0049] In fact, after the modified nanosheets and the cobalt solution are stirred and dispersed to obtain a nanosuspension, it is beneficial to uniformly disperse the modified nanosheets and the cobalt solution in advance, and then adding 2-methylimidazole can promote the in situ growth of ZIF-67 on the surface of the modified nanosheets.

[0050] In some embodiments, when a titanate coupling agent is used to perform surface titanate modification on the surface of ZIF-L(Co) nanosheets, the titanate coupling agent used includes one of PN-130, PN-101, and PN-102. In addition, the mass ratio of the titanate coupling agent used to the ZIF-L(Co) nanosheets is 0.5-4%, which is conducive to uniform modification of the surface of the ZIF-L(Co) nanosheets by the titanate coupling agent.

[0051] In some embodiments, when the surface of the ZIF-L(Co) nanosheet is subjected to surface silane modification treatment using a vinyl silane coupling agent, the silane coupling agent used includes one of KH-540, KH-550, KH-560, KH-570, and KH-602. In addition, the mass ratio of the silane coupling agent used to the ZIF-L(Co) nanosheet is 0.5-4%, which is conducive to uniform surface modification treatment of the ZIF-L(Co) nanosheet by the silane coupling agent.

[0052] In fact, when the surface of the ZIF-L (Co) nanosheet is modified by using a titanate coupling agent or a vinyl silane coupling agent, the titanate coupling agent and / or the silane coupling agent can be dissolved in advance to form an active solution, and then the ZIF-L (Co) nanosheet is infiltrated and modified in the active solution. Specifically, the ZIF-L (Co) nanosheet can be added to the active solution for stirring and mixing or ultrasonic mixing, and then the coupling agent in the active solution is prompted to uniformly modify the surface of the ZIF-L (Co) nanosheet, and then separated and dried. In fact, the solvent in the active solution can be any solvent that can dissolve the titanate coupling agent and / or the silane coupling agent, such as a low molecular alcohol substance, and specifically can be one of methanol, ethanol, and isopropanol.

[0053] In fact, before the modified nanosheets are stirred and dispersed with the cobalt solution, the modified nanosheets can be ultrasonically dispersed in methanol in advance to obtain a uniform modified nanosheet methanol dispersion, and then the modified nanosheet methanol dispersion is mixed with the cobalt solution. Liquid-liquid blending is beneficial to improve the uniformity of the modified nanosheets in the nanosuspension. Specifically, the cobalt solute in the cobalt solution is independent of the cobalt salt used in the preparation of the ZIF-L (Co) nanosheets, and can be one of cobalt nitrate, cobalt propionate, cobalt chloride and hydrates thereof, and the solvent in the cobalt solution can be methanol to adapt to the modified nanosheet methanol dispersion.

[0054] In some embodiments, the concentration of cobalt ions in the cobalt solution is 0.1-4 mol / L. In addition, after 2-methylimidazole is stirred and dissolved in the nanosuspension, the concentration of 2-methylimidazole is 0.1-4 mol / L, and the mass ratio of the modified nanosheet, the cobalt solute in the cobalt solution, and the 2-methylimidazole in the nanosuspension is (0.1-1):1:(5-8).

[0055] The present invention also provides an application of a mixed matrix membrane in gas separation, including separation of a hydrogen and methane mixed gas, and a hydrogen and nitrogen mixed gas.

[0056] Preparation Example 1

[0057] This preparation example 1 provides a method for preparing a composite ZIF framework, comprising the following steps:

[0058] S1. A 0.2 mol / L aqueous solution of cobalt propionate and a 2.2 mol / L aqueous solution of 2-methylimidazole were mixed and stirred at a volume ratio of 1:2 for 4 hours, and then centrifuged and separated. The precipitate was washed and dried in a drying oven at 60° C. for 12 hours, and then ground to obtain ZIF-L(Co) nanosheets.

[0059] S2, after the ZIF-L(Co) nanosheets are infiltrated and modified in a methanol solution containing a PN-130 titanate coupling agent, the modified nanosheets are obtained after centrifugal separation and drying; wherein the mass ratio of the ZIF-L(Co) nanosheets to the PN-130 titanate coupling agent is 100:2;

[0060] S3. Ultrasonic dispersion of the modified nanosheets in methanol for 1 hour, addition of 0.5 mol / L cobalt propionate methanol solution for 1 hour, and then addition of 2.5 mol / L 2-methylimidazole methanol solution for ultrasonic dispersion and reaction for 3 hours, centrifugation, washing the precipitate and drying it in a drying oven at 60°C to obtain a composite ZIF framework; wherein the mass ratio of the modified nanosheets, cobalt propionate and 2-methylimidazole is 0.8:1:5.

[0061] Preparation Example 2

[0062] This Preparation Example 2 provides a preparation method for a composite ZIF framework, which is different from Preparation Example 1 in that the mass ratio of the modified nanosheets, cobalt propionate, and 2-methylimidazole in step S3 is 0.5:1:5.

[0063] Preparation Example 3

[0064] This Preparation Example 3 provides a method for preparing a modified nanosheet, which is different from Preparation Example 1 in that step S3 is not performed.

[0065] Example 1

[0066] This embodiment 1 provides a method for preparing a polyimide mixed matrix membrane, comprising the following steps:

[0067] Y1. Mix polyimide molding powder Vespel SP-1 in N,N-dimethylacetamide and defoam in vacuum to obtain a polyimide glue solution with a solid content of 20%;

[0068] Y2. Add the composite ZIF framework prepared in Preparation Example 1 into the polyimide glue at a mass fraction of 15%, stir and disperse, filter and vacuum defoam, apply it on a smooth and clean glass plate to form a film, and dry it in a vacuum drying oven at 70°C for 8 hours to obtain a polyimide mixed matrix membrane.

[0069] Example 2

[0070] This embodiment 2 provides a method for preparing a polyimide mixed matrix membrane, which is different from the embodiment 1 in that in step Y2, the composite ZIF framework is added with a polyimide glue solution at a mass fraction of 10%.

[0071] Example 3

[0072] This Example 3 provides a method for preparing a polyimide mixed matrix membrane, which is different from Example 1 in that the composite ZIF framework prepared in Preparation Example 2 is used in Step Y2.

[0073] Comparative Example 1

[0074] This comparative example 1 provides a method for preparing a polyimide mixed matrix membrane, which is different from that of Example 1 in that the modified nanosheets prepared in Preparation Example 3 are used in step Y2.

[0075] Comparative Example 2

[0076] This comparative example 2 provides a method for preparing a polyimide mixed matrix membrane, which is different from Example 1 in that in step Y2, the modified nanosheets prepared in Preparation Example 3 with a mass fraction of 1.8% and the metal organic framework ZIF-67 with a mass fraction of 8.2% are mixed and added to the polyimide glue.

[0077] Performance Testing

[0078] The polyimide mixed matrix membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested for permeability and gas separation selectivity based on the method described in GB / T 1038-2000 Test method for gas permeability of plastic films and sheets. The test results are shown in Tables 1 and 2 below.

[0079] Table 1 Permeability test results of polyimide mixed matrix membrane

[0080] <![CDATA[H2 Permeability Coefficient (Barrer)]]> <![CDATA[N2 Permeability Coefficient (Barrer)]]> <![CDATA[CH4 Permeability Coefficient (Barrer)]]> Example 1 16.8 2.13 2.28 Example 2 15.5 1.99 2.14 Example 3 15.9 2.09 2.16 Comparative Example 1 10.3 2.21 2.49 Comparative Example 2 12.5 2.23 2.55

[0081] Table 2 Gas separation selectivity test results of polyimide mixed matrix membrane

[0082]

[0083]

[0084] It can be seen from Tables 1 and 2 that although the mixed matrix membranes prepared in Comparative Example 1 and Example 1 have similar total metal frame loadings, since the modified nanosheets prepared in Comparative Example 1 are not in-situ coated with ZIF-67, they are easily laid flat on one side of the mixed matrix membrane, making it difficult to construct a three-dimensional gas transmission path in the vertical direction. The permeability and separation selectivity are significantly inferior to those of Example 1.

[0085] It can be seen from Tables 1 and 2 that although modified nanosheets and ZIF-67 are compositely added in Comparative Example 2, and although three-dimensional ZIF-67 particles and two-dimensional ZIF-L(Co) nanosheets can be adapted to construct a gas transmission path in the vertical direction, due to the random arrangement of ZIF-67 particles and ZIF-L(Co) nanosheets in the mixed matrix membrane, problems such as uneven mixing are prone to occur, which greatly affects the effect of the constructed gas transmission path. Therefore, although the permeability and separation selectivity of Comparative Example 2 are improved compared with Comparative Example 1, they are significantly inferior to Examples 1 to 3.

[0086] In summary, from Table 1 and Table 2, Figure 1 and Figure 2 It can be seen that the present invention in situ grows three-dimensional ZIF-67 particles on the surface of two-dimensional ZIF-L(Co) nanosheets, which is beneficial to the construction of three-dimensional gas transmission pathways in the vertical direction of the mixed matrix membrane by cobalt-based zeolite imidazole frameworks of homogeneous but different pore sizes, avoiding the problem of simple two-dimensional nanosheets being flattened on the surface of the film in the polyimide mixed matrix membrane, and can effectively improve the gas permeability and selectivity of the mixed matrix membrane.

[0087] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A polyimide mixed matrix membrane, characterized in that The composite ZIF framework is prepared by curing and molding a polyimide mixed matrix glue; the polyimide mixed matrix glue comprises a polyimide glue and a composite ZIF framework dispersed in the polyimide glue, and the composite ZIF framework comprises a ZIF-L (Co) nanosheet and a ZIF-67 in-situ coated on the surface of the ZIF-L (Co) nanosheet.

2. The mixed matrix membrane according to claim 1, characterized in that: The mass fraction of the composite ZIF framework in the polyimide mixed matrix glue is 5-40%; and / or, the polyimide glue comprises a non-protonic polar solvent and a polyimide molding powder dissolved in the non-protonic polar solvent, preferably, the non-protonic polar solvent comprises one of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone, preferably, the polyimide molding powder comprises one of Vespel SP-1, Ultem 1000, Torlon4203, Upimol, and Aurum PL450c; and / or, the solid content of the polyimide glue is 5-25%.

3. The mixed matrix membrane according to claim 1, characterized in that The preparation method of the ZIF-L (Co) nanosheet comprises: mixing and dissolving cobalt salt and 2-methylimidazole, stirring for reaction, separating, washing, drying and grinding to obtain the ZIF-L (Co) nanosheet.

4. The mixed matrix membrane according to claim 3, characterized in that: The cobalt salt includes one of cobalt nitrate, cobalt propionate, cobalt chloride and hydrates thereof; and / or, the molar ratio of the cobalt salt to the 2-methylimidazole is 1:(0.025-4); and / or, after the cobalt salt and the 2-methylimidazole are mixed and dissolved, the concentrations of the cobalt salt and the 2-methylimidazole are independently 0.1-4 mol / L.

5. The mixed matrix membrane according to claim 3 or 4, characterized in that The preparation method of the composite ZIF framework comprises: performing titanate modification and / or silane modification treatment on the surface of a ZIF-L (Co) nanosheet to obtain a modified nanosheet; stirring and dispersing the modified nanosheet in a cobalt solution to obtain a nanosuspension; stirring and dissolving 2-methylimidazole in the nanosuspension and reacting, and then separating, washing and drying to obtain a composite ZIF framework.

6. The mixed matrix membrane according to claim 5, characterized in that: The surface of the ZIF-L(Co) nanosheet is modified with a titanate coupling agent, preferably the titanate coupling agent includes one of PN-130, PN-101, and PN-102, and the mass ratio of the titanate coupling agent to the ZIF-L(Co) nanosheet is 0.5-4%; and / or the surface of the ZIF-L(Co) nanosheet is modified with a vinyl silane coupling agent, preferably the silane coupling agent includes one of KH-540, KH-550, KH-560, KH-570, and KH-602, and the mass ratio of the silane coupling agent to the ZIF-L(Co) nanosheet is 0.5-4%.

7. The mixed matrix membrane according to claim 5, characterized in that: The cobalt solute in the cobalt solution includes one of cobalt nitrate, cobalt propionate, cobalt chloride and hydrates thereof; and / or, the solvent in the cobalt solution includes methanol; and / or, the cobalt ion concentration in the cobalt solution is 0.1-4 mol / L; and / or, after 2-methylimidazole is stirred and dissolved in the nanosuspension, the concentration of the 2-methylimidazole is 0.1-4 mol / L; and / or, the mass ratio of the modified nanosheet, the cobalt solute in the cobalt solution, and the 2-methylimidazole in the nanosuspension is (0.1-1):1:(5-8).

8. The mixed matrix membrane according to claim 1, characterized in that The composite ZIF framework further comprises a modified coating layer, wherein the modified coating layer is located between the ZIF-L(Co) nanosheet and the ZIF-67, and the ZIF-67 is in-situ grown on the surface of the modified coating layer.

9. A method for preparing a mixed matrix membrane according to any one of claims 1 to 8, characterized in that: include: The mixed matrix membrane is prepared by coating the polyimide mixed matrix glue solution into a film and then drying it.

10. Use of the mixed matrix membrane according to any one of claims 1 to 8 or the mixed matrix membrane prepared by the preparation method according to claim 9 in gas separation, characterized in that: The gas separation includes separation of hydrogen and methane mixed gas and separation of hydrogen and nitrogen mixed gas.